Genetic Variation Of Helopeltis Theivora Waterhouse And Its Host Plant Camellia Sinensis L. - Md Latip, Siti Noor Hajjar (2006)

(untitled)
Helopeltis theivora is known as a pest of cocoa and tea in Malaysia. Insecticides have been used for the control of the mirids since cocoa and tea are grown widely in this country. Several mechanisms of insecticide resistance have been proposed and metabolic detoxification was shown to play a major role in insecticide resistance. Although H. theivora is recognized as a leaf-destroying pest of tea, little is known about the genetic background of the mirid, H. theivora and its host plant, tea. This lack of information has lead to the loss of genetic variability and allelic differences of tea clones planted in Malaysia. Little molecular work has been done in H. theivora but some information can be obtained for tea. In a study on the evaluation of the levels infestations of H. theivora on different varieties of tea, the results showed that the tea varieties could be categorized into three different groups namely resistant‚ intermediate and susceptible. For tea, RAPD and RAMs markers were used to study the genetic relationships among the resistant and susceptible varieties found in Bukit Cheeding and Sungai Palas. Both the dendrograms based on the RAMs and RAPD markers‚ respectively grouped the tea varieties into two clusters with the intermediate varieties grouping with the resistant (first cluster) or susceptible (second cluster) varieties. The genetic differences are based on their geographical distributions and partially based on their resistance towards damage by the insect (H. theivora). Two DNA markers were used to identify the genetic variation of H. theivora‚ namely random amplified polymorphic DNA (RAPD) and random amplified microsatellites (RAMs). For RAPD and RAMs markers, after screening 20 arbitary primers, 8 primers were identified as being useful for generating RAPD markers and 5 primers for RAMs markers. A dendrogram obtained through the use of these DNA level markers showed that the first cluster pooled both the populations of H. theivora from BOH estate at Bukit Cheeding and Sungai Palas together while the population of H. theivora from Tanah Rata clustered by itself. This showed that the populations of H. theivora were not clustered together based on their geographical distributions. This clustering pattern could be due to H. theivora (eggs and nymphs) being present on the planting materials from Bukit Cheeding and planted at Sungai Palas since both the plantations are owned by Boh. Eighteen microsatellite primer pairs were designed for H. theivora. Out of these, six were found to be polymorphic (CT2, CT4, CT9, CT15, CT17 and CT18). This study showed that the RAMs technique is suitable and efficient for isolating single locus DNA microsatellites markers for H. theivora.Enzyme studies using inhibitors‚ polyacrylamide gel electrophoresis (PAGE) and gluthatione-s-transferase (GST) analysis using a spectrophotometer were used to identify the metabolic enzymes involved in the development of resistance in H. theivora. The results showed that of the 25 enzymes screened for 8 enzymes were detectable in H. theivora. The dendrogram resulting from the cluster analysis based on isoenzyme data grouped the Bukit Cheeding and the Tanah Rata populations together while the Sungai Palas population clustered by itself. For the Bukit Cheeding and Tanah Rata populations, insecticides were not frequently sprayed when compared with the Sungai Palas population. Esterases and oxidases were enzymes observed to play roles in the insecticide resistance mechanism in H. theivora. Meanwhile, for GST analysis the presence of low activity of GST was detected in H. theivora. This results show that the resistance of H. theivora towards insecticides appeared not to be due to an increased detoxification by gluthatione s-transferase.